Integrated Case Presentation Seminar: Bridging Parallel Fields to Improve Psychiatry and Psychology Learner Experience. - Leffler, Jarrod M.; Romanowicz, Magdalena; Brennan, Elle; Elmaghraby, Rana; Caflisch, Sara; Lange, Hadley; Kirtley, Alexander T. (Child Psychiatry & Human Development, 2024)
Daily clinical practice of mental health professionals often requires interaction between providers from diverse training and professional backgrounds. Efforts to engage mental health trainees across disciplines are necessary and have had varied outcomes. The current study reviews the development and implementation of a monthly one-hour integrated case presentation seminar (ICPS) as part of independent psychology and psychiatry two-year fellowships at a Midwestern teaching hospital. The training integrated a semi-structured seminar to facilitate case presentation within a group setting. The focus of the seminar was to allow for exposure to conceptualization, diagnostic, and treatment strategies and skills, as well as science-based practice techniques for trainees. Learner survey results and the sustained offering of the seminar suggest the format and goals of the seminar are feasible and acceptable. Based on the current preliminary findings, similar training programs may find benefit in strategies to enhance integrated training opportunities for psychiatry and psychology trainees.